QUALITY DETERMINING OF MACHINING PRODUCTS BASED ON MANUFACTURING INDUSTRY STANDARDS: AN EXPLORATION SURVEY OF VOCATIONAL STUDENTS - Bayu Rahmat Setiadi; Setuju Setuju; Suparmin Suparmin (VANOS Journal of Mechanical Engineering Education, 2017)
The quality of a machining product depends on many factors. The manufacturing industry has standardized processes that need to be disseminated to vocational students in order to achieve alignment in the achievement of competence needs relevant to the needs of the industrial world. This study aims to reveal the influential determinant variable in machining process in manufacturing industry and develop conceptual model that can be used as a theory in producing quality products. The research method used survey with exploratory sequential with approach used mix method. The sample of this research is 122 students of National Vocational School Berbah program of machining engineering. Data collection used is questionnaires and interviews. The results showed that there are variables of creativity, completeness of machine accessories, the use of measuring tools, and concerns of occupational health and safety as a critical determinant of the success of a qualified machining process. The Lisrel analysis shows that there are both direct and indirect effects of these variables on the quality of machining products of industry-standard manufacturing.